Effect of immunoglobulin Y formulations on oral microorganisms in human subjects - A systematic review and meta-analysis of clinical trials - Ashwin M Jawdekar; Vatsala Srivastava; Urvashi Tank; Laresh Naresh Mistry (Wolters Kluwer Medknow Publications, 2022)
Background: Passive immunization using egg yolk-based antibodies has been tested against oral microorganisms. Our study assessed the effect of immunoglobulin Y (IgY) formulations on Streptococcus mutans, Porphyromonas gingivalis, and Candida albicans in human subjects. Highlights: VS and UT independently searched articles using keyword combinations in four search engines; studies in English were selected. Either parallel-arm or split-mouth randomized controlled trials on healthy human subjects were considered. Ten studies remained in the selection; six studies compared the effect of IgY formulations on S. mutans, three on P. gingivalis, and one on C. albicans. Five studies (422 subjects) compared the effect of IgY formulations on S. mutans. When fixed-effect model (FEM) was applied, the risk ratio (RR) (confidence interval [CI]) was found to be 7.81 (6.00, 10.18). Three studies (167 subjects) compared the effect of IgY formulations on P. gingivalis. When FEM was applied, the RR (CI) was found to be 0.06 (−0.03, 0.15) in relation to reduction in probing depth. When FEM was applied, for percentage reduction in bleeding on probing (BOP), the RR (CI) was 1.99 (1.64, 2.41). Only one study (26 subjects) was available of IgY formulation and C. albicans; hence meta-analysis was not performed.The search was extended using Google Scholar, Semantic Scholar, cross-references and by contacting authors and researchers in the field which further yielded five articles. . Conclusions: IgY formulations were effective in the reduction of S. mutans. They were not effective on P. gingivalis in relation to probing depth but were effective in relation to reduction in BOP. No harms were reported. Evidence is of low quality due to high heterogeneity. The ROB was moderate and publication bias was low.